(untitled) (Palimpsesto, 2020)
This paper investigates the role of the political-cultural magazines Claves para la interpretación de los hechos and Alternativa Latinoamericana, published in Mendoza (the first between 1970 and 1974, and the second between 1985 and 1990), in the configuration of networks to denounce the human rights violations carried out by the civil-military dictatorships in the countries of the Southern Cone, as well the dissemination of ideas about the processes of transition and return to democracy, and the alternatives of the future for Latin America. It focuses on the relations between Argentina and Chile, and emphasizes those articles that, being censored and / or disseminated clandestinely or underground in their country, found in these journals a space that guarantees the circulation of ideas about the political-social situation Chilean from the coup d’état to Salvador Allende and the denunciations to the dictatorship headed by Augusto Pinochet.